Visual Representation Analysis of Instagram Content @atikoh.s in Support Ganjar Pranowo's 2024 Presidential Campaign - Meydisah Olivia; Ririt Yuniar (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
Instagram is a strategic tool in the political campaign process and is used massively by political spouses, but is often considered only as a tool for image-building or for certain purposes. Siti Atikoh is one of the figures who uses her personal Instagram to support her husband's political strategy. Thus, this study aims to analyze Siti Atikoh's Instagram content, which represents her involvement in the 2024 Presidential Election campaign process, especially to support Ganjar Pranowo's victory. Stuart's representation theory of Hall with a qualitative descriptive approach and visual communication analysis, with data collection techniques through documentation studies of Instagram posts @atikoh.s in the form of photos showing her involvement in the Ganjar Pranowo campaign process during the campaign period (November 2023 - February 2024). The results are first, Siti Atikoh represents herself as a figure of an active "candidate for first lady", cares about social issues, and supports the values of inclusivity and women's empowerment, by the political image built by the Ganjar-Mahfud pair through their ideas; Second, in every campaign post, Siti Atikoh always uses hashtags that are in harmony to strengthen the political message contained in her content. In conclusion, Siti Atikoh not only uses Instagram as an image tool, but she also provides information, education, and persuasion by setting an example through the character values of political figures through subjective experiences, the influence of the social environment, culture, and the ideology she adheres to.